Identifying Important Features of Paratransit Modes in Sylhet City, Bangladesh: A Case Study Based on Travelers Perception - Tanay Datta Chowdhury; Muhammad Saif Uddin; Debolina Datta; Mohammad Azazul Kabir Taraz (Civil Engineering Journal, 2018)
Paratransit modes are familiar modes of transportation in Sylhet city and across Bangladesh. Field investigation marked the existence of motorized, non-motorized and battery driven paratransit modes across city. Though non-motorized vehicles such as rickshaws and easy bike were found in every survey location but people preferred motorized transportation. Young age range people mostly used this media as transportation. Students and service holders were most predominant type of users found from the survey. User satisfaction was used for measuring important characteristics of paratransit modes and the results indicated that about 70% people fall somewhere between satisfied to somewhat satisfied. A Multinomial and an Ordered Logit model were utilized to analyze passenger satisfaction and both of them agreed that female passengers were dissatisfied regarding present paratransit systems. Fitness and cleanliness were considered as influential features of the existing modes. Lack of flexible movement of paratransit modes especially motorized ones around city roads was the main driving force of making the mode unreliable to users. People showed positive attitude towards overall service, safety and security of paratransit vehicles operating in Sylhet city. The fare structure made this transport system popular, but operational shortcomings such as congestion make the prospect of existing modes questionable.